BDNF gene delivery within and beyond templated agarose multi-channel guidance scaffolds enhances peripheral nerve regeneration. (20th October 2016) - Gao, Mingyong; Lu, Paul; Lynam, Dan; Bednark, Bridget; Campana, W Marie; Sakamoto, Jeff; Tuszynski, Mark
Abstract: Objective . We combined implantation of multi-channel templated agarose scaffolds with growth factor gene delivery to examine whether this combinatorial treatment can enhance peripheral axonal regeneration through long sciatic nerve gaps. Approach. 15 mm long scaffolds were templated into highly organized, strictly linear channels, mimicking the linear organization of natural nerves into fascicles of related function. Scaffolds were filled with syngeneic bone marrow stromal cells (MSCs) secreting the growth factor brain derived neurotrophic factor (BDNF), and lentiviral vectors expressing BDNF were injected into the sciatic nerve segment distal to the scaffold implantation site. Main results. Twelve weeks after injury, scaffolds supported highly linear regeneration of host axons across the 15 mm lesion gap. The incorporation of BDNF-secreting cells into scaffolds significantly increased axonal regeneration, and additional injection of viral vectors expressing BDNF into the distal segment of the transected nerve significantly enhanced axonal regeneration beyond the lesion. Significance. Combinatorial treatment with multichannel bioengineered scaffolds and distal growth factor delivery significantly improves peripheral nerve repair, rivaling the gold standard of autografts.